(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Players in the youth category have some shortcomings when passing the ball in short, medium and long distance, which prevents the team from taking effective technical and tactical actions in the game. Given the present needs, the following is formulated: How to improve the passing technique in youth category footballers? With the aim of providing an answer, the objective is to: Identify the main deficiencies in the passing technique of soccer players in the youth category of the Champion’s Claw soccer school. Within the methodology, the qualitative-quantitative method has been considered. The application of a diagnostic test composed of 10 exercises subject to times and successes, allowed to know the current state of practice in the technique of passing the youth category. The techniques belong to the exploratory nature, in order to get to know directly from those involved. In an identical way the field research provided an insight into the soccer school students. The population involved for this study is made up of 35 men and 15 women who belong to the soccer school. From this population group, an intentional non-probabilistic sample was drawn, consisting of 10 men and 8 women. The results showed that the test participants qualitatively the majority border the fair and good. As a conclusion, it is proposed that the youth soccer team of the Champion’s Claw School, through the practice of a structure, exercise and activities, would improve its current condition.